Overweight and Obesity among Recipients of Antiretroviral Therapy at HIV Clinics in Gaborone, Botswana: Factors Associated with Change in Body Mass Index - Jose Gaby Tshikuka; Mgaywa Gilbert Mjungu Damas Magafu; Goabaone Rankgoane-Pono; Julius Chacha Mwita; Tiny Masupe; Shimeles Genna Hamda; Roy Tapera; Mooketsi Molefi; Joseph Tshibangu; John Thato Tlhakanelo (AIDS Research and Treatment)
Background. Factors associated with overweight/obesity among antiretroviral therapy (ART) recipients have not been sufficiently studied in Botswana. Objectives. To: (i) estimate the prevalence and trends in overweight/obesity by duration of exposure to ART among recipients, (ii) assess changes in BMI categories among ART recipients between their first clinic visit (BMI-1) and their last clinic visit (BMI-2), (iii) identify ART regimen that predicts overweight/obesity better than the others and factors associated with BMI changes among ART recipients. Methods. A 12-year retrospective record-based review was conducted. Potential predictors of BMI change among patients after at least three years of ART exposure were examined using a multiple logistic regression model. Adjusted odds ratios (AOR) and their 95% confidence intervals (CIs) were computed. ART regimens, duration of exposure to ART, and recipients’ demographic and biomedical characteristics including the presence or absence of diabetes mellitus-related comorbidities (DRC), defined as any morbidity associated with type 2 diabetes as described in the international statistical classification of diseases and related health problems (ICD-10-CM) codebook index, were investigated as potential predictors of overweight/obesity. Results. Twenty-nine percent of recipients were overweight, 16.6% had obesity of whom 2.4% were morbidly-obese at the last clinic visit. Overweight/obese recipients were more likely to be female, to have DRC and less likely to have CD4 count between 201 and 249 cells/mm3. Neither the first-line nor the second-, third-line ART regimens predicted overweight/obesity better than the other and neither did the duration of exposure to ART. No significant linear trends were observed in the prevalence of overweight/obesity by the duration of exposure to ART. Conclusion. These results suggest that the ART regimens studied have a comparable effect on overweight/obesity and that the duration of exposure does not affect the outcome. This study calls for further research to elucidate the relative contribution of various factors to BMI change among recipients, including ART regimens.